PERSEPSI DAN REAKSI PETANI PADI SAWAH TERHADAP AKTIVITAS PERTAMBANGAN DI DESA JEMBAYAN TENGAH KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA (Perception and Reaction of Lowland Paddy Farmer to Mining Activity in Jembayan Tengah Village Loa Kulu Subdistrict Kutai Kartanegara District) - FITLY RINALDY; SITI BALKIS; TETTY WIJAYANTI (Universitas Mulawarman (University of Mulawarman), 2020)
This research aimed to know the perception and reaction of lowland paddy farmer to mining activity. This research was conducted in Jembayan Tengah Village, Loa Kulu Subdistrict, Kutai Kartanegara District from June to August 2019. Sampling used a purposive method with a total of 30 respondents. Data was be measured by the Guttman scale. The results of this research showed perception of lowland paddy farmer to mining activity was including in the negative category with total score of 28.96. The reaction of lowland paddy farmer to mining activity was including the reject category with total score of 6.53.